PENGARUH MODAL INTELEKTUAL TERHADAP PROFITABILITAS BANK BUMN PERIODE 2015 - 2019 - Azahra Islamadinna; Sujarwo Sujarwo; Elly Mirati (Account : Jurnal Akuntansi, Keuangan dan Perbankan, 2021)
ABSTRACT This study aims to test the hypothesis of the intellectual capital on State Owned Bank Profitability for the 2015-2019 period. Value Added Intellectual Coefficient (VAIC) as model of measurement the intellectual capital performance that used in this study by assessing value added that influenced by capital employed, human capital and structural capital. The analytical method used is multiple regression analysis which is processed using the SPSS version 26. The results of this study partially indicate that Value Added Capital Employed (VACA) and Value Added Human Capital (VAHU) has positive and significant effect on profitability as measured by Return on Assets (ROA) indicator. But on the other hand, Structural Capital Value Added (STVA) does not have a statistically significant effect on profitability as measured by Return on Assets (ROA) indicator. Simultaneously VACA, VAHU, and STVA has a significant effect on profitability as measured by Return on Assets (ROA) indicator. These three variables affect the amount of lending by 43.10%. The remaining 53.9% is explained by other variables not used in this study. Keywords: intellectual capital, profitability, return on assets ABSTRAK Penelitian ini bertujuan untuk menguji hipotesis pengaruh modal intelektual terhadap Profitabilitas Bank BUMN periode 2015-2019. Value Added Intellectual Coefficient (VAIC) merupakan model pengukuran kinerja modal intelektual yang digunakan dalam penelitian ini dengan menilai value added yang dipengaruhi oleh capital employed, human capital dan structural capital. Metode analisis yang digunakan adalah analisis regresi berganda yang diolah dengan menggunakan program SPSS versi 26. Hasil penelitian ini secara parsial menunjukkan Value Added Capital Employed (VACA) dan Value Added Human Capital (VAHU) berpengaruh positif dan signifikan terhadap profitabilitas dengan indikator Return on Assets (ROA). Namun disamping itu Structural Capital Value Added (STVA) tidak berpengaruh signifikan terhadap profitabilitas dengan indikator Return on Assets (ROA). Secara simultan VACA, VAHU, dan STVA berpengaruh signifikan terhadap profitabilitas dengan indikator Return on Assets (ROA). Ketiga variabel tersebut berpengaruh terhadap profitabilitas dengan indikator Return on Assets (ROA) sebesar 43,1%, sisanya sebesar 56,9% dijelaskan oleh variabel lain yang tidak digunakan dalam penelitian ini. Kata Kunci: modal intelektual, profitabilitas, return on assets